RESEARCH OF NEEDS IN DIGITAL SCIENTIFIC AND EDUCATIONAL RESOURCES IN UNIVERSITIES - Rakhmatullaev, Marat (SOCIETY. INTEGRATION. EDUCATION. Proceedings of the International Scientific Conference, 2020)
Currently, without the effective information support of scientific research and the educational process, the innovative development of higher education isn’t possible. But the databases of leading publishers such as Springer Nature, Wiley, Elsevier, Oxford University Press and others are very expensive for universities in developing countries and countries with economies in transition. It is necessary to conduct researches to analyze the demand for digital information resources of publishers to determine the most popular sources for each university. The article is devoted to the results of research on the demand for electronic scientific and educational resources in 63 universities of Uzbekistan, as well as their impact on publication activity. Interviewed more than 1200 respondents from among doctoral students, applicants for academic degrees, teachers and researchers. Based on the results of the survey, the most frequently used sources of information for scientific research, problems they face when writing scientific articles, and information resources they often use are identified. Such researches were conducted in the republic for the first time. The results of the survey made it possible to get a clear picture of the state of information support of universities, to develop recommendations to improve of acquisition funds of academic libraries, on organizing and conducting thematic trainings for doctoral students, teachers, and researchers.